Case report: Pilomatrix carcinoma with PDL1 expression and CDKN2A aberrant - Abula, Ayinuer; Ma, Sheng-Qiang; Wang, Sisi; Peng, Wei; Pei, Xiaming; Hu, Zhe-Yu (Frontiers in Immunology, 2024)
Case Report: A 55-year-old male patient developed a mass in the left inguinal area with left lower limb swelling and first visited a local hospital in three months proir because of unrelieved pain. An MRI scan suggested left suprapubic branch and left acetabular bone destruction, abnormal soft tissue signals within the iliopsoas muscle of the anterior edge of the left iliac bone, and enlarged lymph nodes in the left iliac fossa and left inguinal region. The patient subsequently underwent the left pelvic lesion open biopsy and inguinal lymph node resection biopsy. According to pathological reports, the left inguinal mass was considered to be a malignant tumor of cutaneous accessory origin (pilomatrix carcinoma) with extensive vitreous changes. The suprapupubis branch mass was considered to be a bone metastatic pilomatrix carcinoma. Immunohistochemistry (IHC) revealed a PDL1 combined positive score (CPS) of 8. DNA next-generation sequencing (NGS) showed CDKN2A L65Rfs*53 mutation. The patient received three cycles of gemcitabine and nedaplatin. However, the lesion progressed.Chemotherapy is not effective for treating pilomatrix carcinoma. PDL1 antibodies and CDK4/6 inhibitors might be treatment options for pilomatix carcinoma.